DEVELOPMENT AND VALIDATION OF HPLC-UV METHOD FOR SIMULTANEOUS ANALYSIS OF ACRYLAMIDE AND GLYCIDAMIDE IN VOLUMETRIC ABSORPTIVE MICROSAMPLING - IKHSAN, MUHAMMAD; HARAHAP, YAHDIANA; SAPUTRI, FADLINA CHANY (International Journal of Applied Pharmaceutics, 2022)
Objective: Acrylamide is a carcinogenic compound that can be found in commonly consumed foods and cigarette smoke. This compound is metabolized by cytochrome P450 in the human body to a more reactive metabolite, glycidamide. This study aimed to optimize and validate a sensitive HPLC-UV method for determining acrylamide and glycidamide simultaneously in the volumetric absorptive microsampling (VAMS) sample. Methods: Isoniazid as an internal standard was added to the VAMS sample containing acrylamide and glycidamide prior to protein precipitation. The analytes and internal standard were separated using reversed-phase chromatography with the C18 SunfireTMWaters® column (5 µm; 250 mm x 4.6 mm) and an ultraviolet detector. Results: The optimum chromatographic condition was eluted at a column temperature of 30 °C with a mobile phase of 6 mmol potassium dihydrogen phosphate pH 3.5–methanol (96:4 v/v) using a flow rate of 0.50 ml/min and was detected at 210 nm. The LLOQ was obtained at 1.0 µg/ml for both acrylamide and glycidamide. The calibration curve was linear over the concentration range of 1.0-100.0 µg/ml. Conclusion: The developed bioanalytical method was valid based on US FDA Guideline for Bioanalytical Method Validation 2018.